Effect of adiposity and physical fitness on cardiometabolic risk factors in adolescents: A 2-year longitudinal study - Karah J. Dring; Simon B. Cooper; Ryan A. Williams; John G. Morris; Caroline Sunderland; Gemma A. Foulds; A. Graham Pockley; Mary E. Nevill (Frontiers in Sports and Active Living, 2022)
Although risk factors for cardiometabolic diseases begin to present in young people, the association between physical fitness and adiposity with traditional and novel risk factors for cardiometabolic diseases across adolescence remains relatively unknown. Following ethical approval, fifty-two adolescents (age 11.6 ± 0.6 years; 32 girls) were recruited for a 2-years longitudinal study. Adiposity was assessed based on sum of skinfolds, waist circumference and body mass index, and physical fitness as distance run on the multi-stage fitness test (MSFT). Risk factors for cardiometabolic diseases (pro- and anti-inflammatory cytokines, plasma insulin, Homeostatic Model Assessment of Insulin Resistance - HOMA-IR, blood pressure) were measured following an overnight fast. Relationships between independent and response variables were analysed using multi-level modelling (final combined models were created using the stepwise backward elimination method). Plasma insulin concentration and HOMA-IR were positively associated with adiposity and inversely associated with distance run on the MSFT (all p < 0.05). The final combined models for plasma insulin concentration and HOMA-IR contained main effects for age, skinfolds and distance run on the MSFT. Levels of the anti-inflammatory cytokine IL-10 were inversely related to the sum of skinfolds (p = 0.046), whereas there was a trend for levels of the pro-inflammatory cytokine TNF-α to be positively related to the sum of skinfolds (p = 0.056). Adiposity and physical fitness are important, independent, determinants of metabolic health in adolescents. Furthermore, adiposity influences levels of pro- and anti-inflammatory cytokines in adolescence, with greater adiposity associated with a poorer inflammatory profile. The present study demonstrates an independent effect of physical fitness on metabolic health longitudinally across adolescence. It is therefore recommended that future work develops therapeutic interventions that reduce adiposity and enhance physical fitness in adolescents, to promote lifelong health.